KESAN PERTAMA DAN KOGNISI SOSIAL: VALIDASI LINTAS BUDAYA, REPLIKASI DAN KEMAJUAN METODOLOGIS - Dini Mahfudzah Aulia; Ozi Rahmadani; Dwi Rahmadani; Wafis Marsella; Nafizah Putri; Sugeng Sejati (CV. BAROKAH PUBLISHER, 2026)
First impressions are a crucial initial process in social interactions. In the study of social cognition, this process involves mental mechanisms that enable individuals to understand, interpret, and respond efficiently to the social environment. Social cognition plays a role in explaining broader psychological phenomena, such as interpersonal communication, social emotions, and adjustment after specific events. Indonesia's cultural diversity demonstrates that social perception is not always universal. Local values, social norms, and cultural backgrounds influence how individuals form and interpret first impressions. Therefore, cross-cultural validation is an important aspect of social cognition to ensure the relevance of developed theories in both Indonesian and global contexts. Replication results generally indicate that although there are common patterns in judging others, such as a tendency to use visual information, interpretations can still differ depending on the context. Therefore, replication is crucial for strengthening the validity of social cognition theories and understanding biases and misperceptions in social interactions. Methodological advances in social cognition research indicate a shift from traditional models to more integrative approaches, such as connectionist models